2021
DOI: 10.1371/journal.pntd.0009627
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal vaccine from whole Leishmania donovani antigens provides protection and induces specific immune response against visceral leishmaniasis

Abstract: Visceral leishmaniasis is a protozoan disease associated with high fatality rate in developing countries. Although the drug pipeline is constantly improving, available treatments are costly and live-threatening side effects are not uncommon. Moreover, an approved vaccine against human leishmaniasis does not exist yet. Using whole antigens from Leishmania donovani promastigotes (LdAg), we investigated the protective potential of a novel adjuvant-free vaccine strategy. Immunization of mice with LdAg via the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…5A . For this purpose, we prepared splenocytes from the above-described treated mice on the 48th day postinfection, restimulated these cells with soluble L. donovani antigens (SLA) for 48 h ( 40 , 41 ), and assessed the frequencies of type 1 (interferon gamma [IFN-γ] and TNF-α) and type 2 (IL-10) cytokine-producing CD4 + or CD8 + T cells via intracellular staining, followed by flow cytometry. We found that the frequencies of CD4 + and CD8 + T cells expressing IFN-γ and TNF-α were increased and those expressing IL-10 were decreased (also noted by another group [ 38 ]) in the spleens of L. donovani -infected mice following adoptive transfer of LPS-treated but not control (PBS)-treated DCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A . For this purpose, we prepared splenocytes from the above-described treated mice on the 48th day postinfection, restimulated these cells with soluble L. donovani antigens (SLA) for 48 h ( 40 , 41 ), and assessed the frequencies of type 1 (interferon gamma [IFN-γ] and TNF-α) and type 2 (IL-10) cytokine-producing CD4 + or CD8 + T cells via intracellular staining, followed by flow cytometry. We found that the frequencies of CD4 + and CD8 + T cells expressing IFN-γ and TNF-α were increased and those expressing IL-10 were decreased (also noted by another group [ 38 ]) in the spleens of L. donovani -infected mice following adoptive transfer of LPS-treated but not control (PBS)-treated DCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the 48th day postinfection, the spleens and livers were removed from these mice to measure their weights and the parasite load. In addition, splenocytes (1 × 10 6 /well) derived from these mice were subsequently stimulated with SLA (80 μg/mL) for 48 h or left unstimulated ( 40 , 41 ), and the percentages of splenic CD4 + and CD8 + T cells expressing type 1 (IFN-γ and ΤΝFα) or type 2 (IL-10) cytokines were determined via flow cytometry. To detect type 1 and type 2 cytokine expression in CD4 + and CD8 + T cells, splenocytes were surface stained with anti-CD3-APC along with anti-CD4-FITC (or -PerCP/Cy5.5), anti-CD8-PerCP/Cy5.5 (or -FITC), or the respective isotype control antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike most parasitic infections, protective immunity occurs against reinfection in patients who recover from leishmaniasis or following leishmanization (LZ) [ 16 , 17 ]. This result reveals that immunological mechanisms play a major role in shaping the disease, and this globally important disease can potentially be prevented using vaccines [ 8 , 18 , 19 ]. It also provides a roadmap for the development of successful vaccines that can generate protective immunity against infection [ 20 ].…”
Section: The Role Of Immunological Mechanisms In Leishmaniasismentioning
confidence: 99%
“…However, these studies show that they induce a weaker Th1 type immune response than live parasites, and the results are associated with an inconsistent effect. For these reasons, adjuvants have been used in many studies (e.g., Bacillus Calmette–Guérin (BCG)), and the parasites have been administered through alternative routes such as the mucosal route [ 19 , 39 , 49 ].…”
Section: Vaccination Strategies In Leishmaniasismentioning
confidence: 99%
“…Many distinct VL vaccine candidates have been tested in murine and/or canine models [ 13 , 14 , 15 , 16 ], including plasmid DNA-based [ 17 , 18 ] and recombinant protein-based vaccines [ 19 , 20 ]. However, few have progressed to human trials, and the use of individual Leishmania proteins as recombinant molecules limits the antigenic repertoire of the experimental vaccines.…”
Section: Introductionmentioning
confidence: 99%